Investigation of hybridized bluff bodies for flow-induced vibration energy harvesting - Wang, Junlei (2023)
Small-scale wind energy harvesting based on flow-induced vibration (FIV) mechanisms has attracted lots of research interest in recent years. Vortex-induced vibration (VIV) and galloping energy harvesters usually outperform each other in different wind-speed ranges. To combine the advantages of VIV and galloping harvesters, this paper explores the idea of using a hybridized bluff body constituting of two cylindrical and one cuboid segment for wind energy harvesting. The total length of the hybridized bluff body was fixed. The cuboid segment length was varied to investigate the effect on the FIV behavior of the bluff body. The results show that, when the cuboid segment is short in length, the bluff body exhibits VIV-like behavior in the low wind-speed range and galloping-like behavior in the high-speed range. In the medium wind-speed range, galloping-VIV coupling appears. However, if the cuboid segment is longer, the galloping-VIV coupling phenomenon disappears; the hybridized bluff body behaves just like a cuboid one and only exhibits a galloping motion. In addition to experiments, computational fluid dynamics (CFD) simulations are also conducted to provide more insights into the aerodynamics of the hybridized bluff body. The simulation results reveal that introducing hybridization into the bluff body changes the vorticity flow behind it and alters the vortex-shedding behavior. The vortex-shedding effect, in turn, affects the vibration of the bluff body, as well as the performance of the harvester.